Research Collaboration and Epistemic Gaps in Public Sector Financial Sustainability: A Global Bibliometric Perspective - Lekettey, Edem; Nugraha, Nugraha; Sari, Maya (Dinasti Publisher, 2025)
This study examines trends in international cooperation within Local Government Financial Sustainability (LGFS) research, a discipline that is becoming increasingly significant owing to the financial difficulties encountered by subnational governments and the need for equitable governance in accordance with Sustainable Development Goals (SDGs). Despite ongoing studies, disparities persist in the involvement of industrialized versus developing nations in LGFS research. This study uses bibliometric methodology with 627 Scopus-indexed data from 2007 to 2025 and VOSviewer to illustrate the co-authorship and keyword networks. Richer countries like the US, UK, and Australia are at the heart of the core-periphery structure, according to the research, while underdeveloped countries are mostly unrepresented on the periphery. Prominent writers and advocacy organizations are within European institutions. The Global South provides only limited intellectual guidance. Keyword co-occurrence mapping shows a shift during the COVID-19 epidemic from austerity and accountability to decentralization and governance. This study revealed disparities in worldwide LGFS research networks, potentially benefiting from donor-driven initiatives. It advocates equal co-authorship policies, enhanced training in underrepresented fields, and open-access distribution to promote inclusive knowledge advancement. The results provide guidance for establishing a framework for global and regional cooperation.